“Religious” as a Category: A Comparative Case Study - Campany, Robert Ford (Numen, 2018)
Rightly noting that premodern non-Western cultures lacked a version of the modern Western category of “the religious,” some scholars have proposed simply abandoning it. Meanwhile, other scholars continue to wield it uncritically. In this article I propose a middle way, using premodern China as an example. Although China had no category exactly matching “the religious” in meaning and scope, it did, I argue, have an analogous category, one that functioned somewhat similarly in a partially analogous discourse that, like the Western category, formed part of an imperial project. More generally, I suggest that we do well to inquire into the extent to which the cultures we study possessed analogues to the categories and concepts in terms of which we characterize them, rather than assume either that they did or that they did not.